PENGEMBANGAN METODE PEMASARAN MELALUI DIGITAL MARKETING BAGI PRODUK UMKM DI NAGARI KAMANG MUDIAK KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Asniati Bahari; Devi Yulia Rahmi; Jefril Rahmadoni; Khairil Anwar (Jurnal Hilirisasi IPTEKS, 2022)
Digital marketing is the marketing of goods or services that are targeted, measurable, and interactive by using digital technology to reach many consumers. Through the scheme to build a Nagari at Andalas University, the authors carry out service by providing socialization and direct digital marketing practices to MSME actors. This activity is very necessary, considering that SMEs in Nagari Kamang Mudiak, Kamang Magek District, Agam Regency, have been doing traditional marketing through direct sales to consumers. Thus, this training was carried out for MSME actors in the Kamang Mudiak village. The purpose of this activity is to (1) provide knowledge as well as training to MSME actors to increase the marketing of MSME products with digital marketing methods, (2) increase the knowledge of MSME actors in Nagari Kamang Mudiak related to the types of digital marketing, and (3) MSMEs are able to market their products digitally. This activity is carried out using the lecture method and then the participants practice directly how to do product marketing digitally with their respective social media. The training which was attended by 36 participants succeeded in achieving the goal because the participants were able to market their products with various types of digital marketing media through WhatsApp Business, Facebook Marketplace, Instagram and Shopee. After training, MSME actors can place their own using WhatsApp Business, Facebook Marketplace, Instagram and Shopee. MSME actors and the nagari government hope that service activities like this will continue to be carried out in the context of business continuity for MSME actors in Kamang Mudiak Nagari.